Los fondos bibliográficos antiguos del Monasterio de la Inmaculada Concepción de León (Estudios humanísticos. Geografía, historia y arte, 1993)
It deals with libraries and readers' situation during Modern Age in León, paying attention to ecclesiastic libraries. After an historic introduction of the Inmaculada Concepción Monastery in León, its antique books are studied: number, date of edition, main printing houses, chief authors, subjects, languages, origins and illustrations.